Suppression of Inflammation Delays Hair Cell Regeneration and Functional Recovery Following Lateral Line Damage in Zebrafish Larvae - Ru Zhang; Xiaopeng Liu; Yajuan Li; Ming Wang; Lin Chen; Bing Hu (Biomolecules, 2020)
Cochlear hair cells in human beings cannot regenerate after loss; however, those in fish and other lower species can. Recently, the role of inflammation in hair cell regeneration has been attracting the attention of scientists. In the present study, we investigated how suppression of inflammatory factors affects hair cell regeneration and the functional recovery of regenerated hair cells in zebrafish. We killed hair cells in the lateral line of zebrafish larvae with CuSO4 to induce an inflammatory response and coapplied BRS-28, an anti-inflammatory agent to suppress the inflammation. The recovery of the hair cell number and rheotaxis was slower when CuSO4 and BRS-28 were coapplied than when CuSO4 was applied alone. The recovery of hair cell count lagged behind that of the calcium imaging signal during the regeneration. The calcium imaging signal in the neuromasts in the inflammation-inhibited group was weaker than that in the noninflammation-inhibited group at the early stage of regeneration, although it returned to normal at the late stage. Our study demonstrates that suppressing inflammation by BRS-28 delays hair cell regeneration and functional recovery when hair cells are damaged. We suspect that BRS-28 inhibits pro-inflammatory factors and thereby reduces the migration of macrophages to delay the regeneration of hair cells.